Effects of immunosuppressive therapy on wound healing. Issue 1 (24th February 2012) - Bootun, Roshan
<x xml:space="preserve">Abstract</x> Immunosuppressive therapy is increasingly being used in clinical practice and has been shown to affect wound healing to varying degrees. This article looks at the effects of the newer immunosuppressive agents on wound healing. It is shown that wound healing is impaired via different mechanisms. Some of the animal and human studies are reviewed in more detail. It is shown that some of the newer agents affect wound healing to such an extent that reduction or avoidance of these drugs until complete wound healing is achieved is advocated. More research is required for these newer agents to determine the most appropriate time to introduce them.